ESG Performance, Research and Development Investment and Enterprise Green Technology Innovation - Hu Jie; Zhang Xueer (SHS Web of Conferences, 2023)
Based on the panel data of China's Shanghai and Shenzhen A-share industrial listed companies from 2014 to 2021, this paper constructs A fixed-effect model to investigate the influence of ESG performance on enterprises' green technology innovation, and constructs a mediating effect model to explore the mediating role of R&D investment in the influence of ESG performance on enterprises' green technology innovation. The results show that good ESG performance has a significant promoting effect on enterprises' green technology innovation. And there is an intermediary path for R&D investment. It means that ESG promotes enterprise green technology innovation through R&D investment. Finally, the conclusions of this paper passed the robustness test and endogeneity test. This paper opens up a new research perspective and provides theoretical and empirical experience for enterprises to achieve sustainable development in the future.